Beneficial Hypoglycemic, Hypolipidemic Effects of Aerial Branches and Roots Extract of Eryngium caeruleum M. Bieb on Streptozotocin-Induced Diabetes Model in Rats - Aryaneh Sardarbandeh; Mohammad Reza Delnavazi; Mohammad Sharifzadeh; Masoumeh Ghajarieh Sepanlou; Zahra Tamiji; Seyede Nargess Sadati Lamardi (Tehran University of Medical Sciences, 2021)
Eryngium caeruleum (Apiacea) is native to the northern forests of Iran. The anti-diabetic effect of other species of the genus Eryngium has already been reported in previous studies. In this study, the anti-diabetic effect of this extract on animal blood lipid factors was investigated. Hydroalcoholic extract was obtained from different parts of the plant, including roots, leaves, and aerial branches with fruits were prepared by maceration with 70% ethanol. Oral acute toxicity of the extracts was assayed in different doses of 2000, 4000, and 8000 mg/kg in rats. To induce diabetes in the studied animals, 60-70 mg/kg of streptozotocin (STZ) was injected intraperitoneally (IP). For the purpose of this study, 72 male Wistar rats were randomly divided into different groups of normal, diabetic, and positive controls (metformin 500 mg/kg) as well as 9 diabetic groups that orally received 200, 400, and 800 mg/kg of extracts. The effects of the treatment with extracts for a 14-day period were investigated on weight, blood glucose, and lipid profile. By comparing the control groups with the groups of hydroalcoholic extracts of E. caeruleum showed that the most effective sample on weight gain and also on reducing blood glucose was the group receiving 800 mg/kg of the aerial branches extract (P < 0.01 and P < 0.001, respectively) after 14 days. As well, the most effective sample on lowering the blood lipid factors was the hydroalcoholic extract of the root of E. coareleum with a dose of 200 mg/kg, which showed a significant effect on lowering total cholesterol in diabetic rats compared to the diabetic controls (P < 0.05). Hydroalcoholic extract of leaves with 200 mg/kg also showed a better effect on lowering the LDL and VLDL levels compared to the diabetic control group (P < 0.001). The results of pancreatic histology in the samples showed that the extracts of the aerial branch and root (800 mg/kg) had significant effects on the regeneration of the islets of Langerhans compared to the diabetic control group. In conclusion, E. caeruleum could significantly improve glycemic and lipid profiles in diabetic rats.